TAMING THE WOLF WITHIN: Role of Religion in Countering Political Violence - Chittilappilly, Paul Chummar (Journal of Dharma, 2009)
“Peace Breaker – Peace Maker” is the challenging poster for International Women’s Day on 8th of March 2010 here in Kenya, a nation where more than 10,000 Kenyans still remaining in limbo after the Post-ElectionViolence in Kenya 2007-20081. During this period more than 1500 people were ruthlessly killed and more than 250,000 were displaced. Although the barbarous forms of fresh acts of violence and slaughter of fellow Kenyans has ceased, violence in the name of a particular tribe or political party or religious affiliation is still on the agenda of many Sub-Saharan countries, like Somalia, Chad, Sudan, Zimbabwe and Democratic Republic of Congo as well as in South Asian countries such as Afghanistan, Pakistan and India. Hardly any of the 195 nations of our global village are without any conflict whether political, religious, ethnic, or self-interest or a combination of these factors. Many people in these countries are wounded and distressed to the depth of their souls, and, to certain extent, angry and revengeful. The number of political and religious martyrs continues to grow throughout the world. The spiral of violence goes up and up! Although the conflicts start with the differences of interests, demands, feelings, aims, ideologies, values, norms, roles, systems, or activities etc., every conflict has a personal character and every violent act is carried out by people, person against person, person against society, or even person against nature. Violence is a human reality, as old as human history!